1997
DOI: 10.1007/bf02478870
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoplasmacyte-rich meningioma: A case report with histological and immunohistochemical studies

Abstract: This report concerns a 64-year-old woman with a lymphoplasmacyte-rich meningioma. Radiographically and macroscopically, the tumor had the appearance of an ordinary meningioma. Components of the meningothelial cells were positively immunostained for epithelial membrane antigen. The results of immunohistochemical assays with the antibodies to surface markers of lymphocytes L26 and UCHL-1 indicated that the lymphoplasmacellular proliferation was not neoplastic but probably represented an immune reaction of the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…[ 9 ] Immunohistochemical assays indicated that the lymphoplasmacellular proliferation probably represents an immune reaction of the host. [ 10 ] However, the relationship between inflammatory lesions and meningiomas remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Immunohistochemical assays indicated that the lymphoplasmacellular proliferation probably represents an immune reaction of the host. [ 10 ] However, the relationship between inflammatory lesions and meningiomas remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…The classical appearance of this lesion is a slowly growing, rubbery, well demarcated, rounded nodule with a broad dural attachment, arising over the cerebral convexities, often parasagittal in association with the falx and venous sinus. Other sites include sphenoid ridges, olfactory grooves, parasellar regions, petrous ridges, tentorium and posterior fossa (2,3,8,9,12,13,19) .…”
Section: Discussionmentioning
confidence: 99%
“…There is often a background of predominantly B-cell lymphocytes (CD20 positive) and a minor population of CD3-positive T cells. Idiopathic hypertrophic pachymeningitis is a disease in which there is thickening of the dura, enhancement on appropriate imaging studies, and no microorganisms or other inflammatory disease are recognized (1,2,4,5,11,13,14,(16)(17)(18) .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still some controversy about whether it represents a distinct entity, as its behavior often resembles that of an inflammatory condition 2,3 . The clinicopathological features of patients with LPM vary in terms of tumor location, age, clinical prognosis and the biological behavior of the tumor cells 2–14 . Systemic hematological abnormalities, including hyperglobulinemia and iron refractory anemia have been documented in some patients with LPM 6,7,13 .…”
Section: Introductionmentioning
confidence: 99%